Penerapan Metode Total Productive Maintenance Dan Overall Equipment Effectiveness Pada Mesin Sterilizer Di PT. Tri Cahaya Sawit - Sihombing, Roy Aldo; Situmorang, Zefanya; Tampubolon, Jusra (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2025)
Machine effectiveness is a critical factor in ensuring smooth operations within the palm oil processing industry. One of the most vital machines in this process is the sterilizer, which functions to deactivate enzymes, soften fruit, and facilitate the detachment of fruit bunches. This study aims to evaluate the effectiveness level of the sterilizer machine at PT. Tri Cahaya Sawit using the Overall Equipment Effectiveness (OEE) method and to propose an improvement strategy based on Total Productive Maintenance (TPM). This research adopts a quantitative case study approach with descriptive analysis. Data were collected through direct observation, interviews, and company documentation from March to June 2024. The three OEE parameters analyzed include availability, performance, and quality rate. The results showed an average OEE value of 82.5%, with an availability rate of 92.67%, performance rate of 91.87%, and quality rate of 97.43%. These figures remain below the world-class OEE benchmark of 85%. The primary factors contributing to low effectiveness were high downtime and suboptimal maintenance scheduling. Fishbone diagram analysis revealed that the dominant causes included reactive maintenance practices, lack of operator training, and inadequate maintenance documentation. Therefore, the implementation of the eight TPM pillars—particularly autonomous maintenance and planned maintenance—is proposed to enhance the reliability and efficiency of the sterilizer machine. This study concludes that OEE serves as an effective evaluation tool to identify operational losses, and a structured TPM implementation can significantly improve machine performance and overall company productivity. Keywords: Total Productive Maintenance, Overall Equipment Effectiveness, Sterilizer Machine, Downtime, Productivity.